Global Earnings Inequality, 1970 2015 - Olle Hammar; Daniel Waldenström (Institute of Labor Economics (IZA), 2017)
We estimate trends in global earnings dispersion across occupational groups using a new database covering 66 developed and developing countries between 1970 and 2015. Our main finding is that global earnings inequality has declined, primarily during the 2000s, when the global Gini coefficient dropped nearly 10 points and the earnings share of the world's poorest half doubled. Decomposition analyses emphasize the role of income convergence between poor and rich countries and that earnings have become more similar within occupations in traded industries. Sensitivity checks show that the results are robust to varying real exchange rates, inequality measures and population definitions.
Keywords: D31; F01; O15; 330; global inequality; development; inequality decomposition; labor markets